2022
DOI: 10.3847/1538-4357/ac7568
|View full text |Cite
|
Sign up to set email alerts
|

The Panchromatic Hubble Andromeda Treasury: Triangulum Extended Region (PHATTER). II. The Spatially Resolved Recent Star Formation History of M33

Abstract: We measure the spatially resolved recent star formation history (SFH) of M33 using optical images taken with the Hubble Space Telescope as part of the Panchromatic Hubble Andromeda Treasury: Triangulum Extended Region (PHATTER) survey. The area covered by the observations used in this analysis covers a de-projected area of ∼38 kpc2 and extends to ∼3.5 and ∼2 kpc from the center of M33 along the major and semimajor axes, respectively. We divide the PHATTER optical survey into 2005 regions that measure 24 arcsec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 98 publications
1
56
0
Order By: Relevance
“…We have shown that the extinction corrections made by Massey et al (2021b) were a little too high based upon the inferred temperatures for M2-3 I RSGs. Instead, we have recomputed the luminosities by adopting a uniform reddening for each galaxy based on the average values from the M31 PHAT (Dalcanton et al 2012(Dalcanton et al , 2015 and M33 PHATTER (Williams et al 2021;Lazzarini et al 2022) studies. Given that we are using these A V values to compute corrections to K, the differences in luminosities are slight in comparison with Massey et al (2021b), except for the brightest RSGs, where we have argued that Massey et al (2021b) overcorrected the data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that the extinction corrections made by Massey et al (2021b) were a little too high based upon the inferred temperatures for M2-3 I RSGs. Instead, we have recomputed the luminosities by adopting a uniform reddening for each galaxy based on the average values from the M31 PHAT (Dalcanton et al 2012(Dalcanton et al , 2015 and M33 PHATTER (Williams et al 2021;Lazzarini et al 2022) studies. Given that we are using these A V values to compute corrections to K, the differences in luminosities are slight in comparison with Massey et al (2021b), except for the brightest RSGs, where we have argued that Massey et al (2021b) overcorrected the data.…”
Section: Discussionmentioning
confidence: 99%
“…For M33, the extinctions for multiple regions was measured in a similar manner using the Panchromatic Hubble Andromeda Treasury: Triangulum Extended Region (PHATTER; Williams et al 2021) data set (Lazzarini et al 2022). The average roughly corresponds to a value of A V = 0.8 mag (M. Lazzarini 2022, private communication).…”
Section: Revisiting the Extinction Correctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our larger sample and more homogeneous photometry catalog allow us to compare different fitting methods and quantify the impact these changes have on the age and mass results. Additionally, we compare our custom SNR-centered SFHs to those measured by Lazzarini et al (2022) in grids, allowing us to determine whether grid SFHs are sufficient for inferring a progenitor age and mass. The rest of the paper is outlined as follows: Section 2 details our SNR source catalog, as well as how our SFHs were measured.…”
Section: --+mentioning
confidence: 99%
“…Overall, this exercise shows that the star formation differences between M31 and M33 are likely significant enough to impact cluster populations. We look forward to using robust star formation history fitting (Lazzarini et al 2022) to inform recent SFR and Σ SFR determinations for M33, and aid future Γ determinations for the PHATTER cluster sample.…”
Section: Catalog Comparison Summarymentioning
confidence: 99%